Awareness of Financial Inclusion: An Empirical Study in Tiruttani Taluk, Thiruvallur District, Tamil Nadu. - Dr. S Subramanian, V R Govindan, (European Economic Letters (EEL), 2024)
The Indian government consistently makes efforts to include rural people in the organized financial system. This initiative not only boosts the Indian economy by encouragement of savings habit, but also facilitates rural development through access to banking facilities, services like gas subsidies etc. The term “financial inclusion” may vary under different ruling parties, but the primary objective remains consistent: to uplift the bottom of the financial market pyramid. The current state of affairs indicates that the present government has achieved some success by opening approximately 12.54 crore new bank accounts (as of January 2015) and accumulating deposits of over Rs. 5000 crore (up to November 2014) through the Pradhan Mantri Jan Dhan Yojana (PMJDY), a new form of financial inclusion. However, it is evident that a significant portion of the rural market remains untapped and under-explored. Therefore, this paper aims to explore the awareness of financial inclusion schemes among rural customers in Tiruvallur District, Tamil Nadu. The study seeks to understand how effectively these initiatives are reaching the intended beneficiaries and identify areas for improvement. By enhancing awareness and accessibility, we can further empower rural communities and promote inclusive economic growth.